Newly described weathering pattern in pili annulati hair shafts: a scanning electron microscopic study. - Feldmann, K; Dawber, R; Pittelkow, MR; Ferguson, D (2001)
Certain scalp hair shafts from 2 of 10 cases of pili annulati examined by scanning electron microscopy exhibited an unusual weathering pattern. The majority of affected hair shafts showed minor surface abnormalities at regular intervals (nodes) associated with the underlying spaces. However, in a few examples, there was marked damage to the cuticle at the nodes exposing the underlying cortex; in severe cases there was cracking of both cuticle and cortex. These damaged nodes were also associated with trichorrhexis nodosa-like breaks of the hair shaft. This study shows that the nodes in pili annulati may have some inherent weakness that could result in breaks in the hair shaft exposed to physical trauma.